Competitive Intensity dan Struktur Modal - Dwi Wahyu Lestari; Fina Khoirotul Badi’ah; Axel Giovanni (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The aim of this research is to examine the effect of competitive intensity on capital structure, with profitability as a control variable. The type of research used in this study is quantitative with an associative approach. The sample for this research was taken using a purposive sampling method, and a sample of 20 companies was obtained that met the research criteria. The data analysis technique used in this research is multiple linear regression analysis. The results of this research show that competitive intensity has an influence on capital structure.